NONLINEAR MODELING OF CONFINED MASONRY STRUCTURES USING LAYERED SHELL ELEMENTS (Jurnal Ilmiah Teknik Sipil, 2026)
Confined masonry structures are widely used in simple buildings located in seismic regions; however, their behavior is difficult to represent numerically because masonry is heterogeneous and nonlinear. This study evaluates layered shell elements in SAP2000 for modeling the global response of confined masonry, analyzes the influence of material parameters, and compares a simple building model based on the guideline of the Ministry of Public Works and Housing of Indonesia (PUPR), hereafter referred to as CM, with an Earthquake Engineering Research Institute (EERI)-based modified model, hereafter referred to as CME. The CME model includes additional reinforcing columns and beams around wall openings. Validation was conducted using two-dimensional and three-dimensional models based on previous laboratory experiments. The investigated parameters include masonry compressive strength (f'm), masonry elastic modulus (Em), masonry shear modulus (Gm), and concrete compressive strength of confining elements (f'c). The results show that layered shell elements can represent the global response of confined masonry structures, particularly initial stiffness, lateral capacity, and stress concentration patterns, although the analysis was conducted using monotonic pushover loading. The sensitivity analysis indicates that the parameter influence, from the lowest to the highest, is f'c, f'm, Em, and Gm. In the application model, both CM and CME reach the Immediate Occupancy (IO) performance level. However, CME produces smaller drift, higher lateral capacity, and a more uniform wall stress distribution than CM. Therefore, the EERI-based modification can increase lateral capacity and control local damage in confined masonry structures.
Keywords: confined masonry structure; EERI; layered shell; material sensitivity; pushover